Preparation and characterizations of glyceryl oleate ufasomes of terbinafine hydrochloride: a novel approach to trigger Candida albicans fungal infection - Sankha Bhattacharya (SpringerOpen, 2021)
Abstract Background Worldwide fungal infection cases are increasing by leaps and bounds. The patients who are immunocompromised, i.e., cancer and AIDS, are more susceptible to different types of fungal infections like cutaneous candidiasis and its associate infections. The available treatment for such a disease is creams, gels, etc. However, due to the lack of penetrability and higher systematic absorption, these formulations have reported many side effects. To overcome such challenges, various novel drug delivery systems were introduced. The present research focused on the preparation of glyceryl oleate ufasomes of terbinafine hydrochloride using the film hydration method. Result The prepared formulations were characterized for globular size (nm), zeta potential (mV), PDI, morphological characteristics, thermal behavior, in vitro drug release, in vitro antifungal activity, and in vitro skin permeation retention studies. After suitable formulation optimization using thin-film hydration method, 3:7 drug to glyceryl oleate ratio, UF3 formulation was found to produce higher drug entrapment efficacy (52.45 ± 0.56%), stable anionic zeta potential (− 33.37 ± 0.231 mV), desired globular size (376.5 ± 0.42 nm), and decent polydispersity index (0.348 ± 0.0345). Diffusion-controlled and zero-order sustained release profile was observed in the optimized UF3 batch. From the 5 days in vitro antifungal activity studies, it confirmed that UF3 ufasomes possessed good applicability in more prolonged therapy. Conclusion From the current investigation, it can be concluded that glyceryl oleate ufasomes of terbinafine hydrochloride could be an excellent approach to treat topical fungal infections.